2005
DOI: 10.1016/j.jcrs.2004.12.045
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of nerve fiber layer thickness before and after laser in situ keratomileusis using scanning laser polarimetry with variable corneal compensation

Abstract: These data suggest that SLP-VCC mean thickness measurements are not influenced by LASIK-induced alterations in corneal architecture. Measurements obtained with SLP-VCC before surgery may be used for future comparisons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
8

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
1
6
0
8
Order By: Relevance
“…42 Measurement of retinal nerve fiber layer thickness in healthy patients undergoing LASIK suggests that exposure to IOP greater than 60 mm Hg for periods up to 45 seconds does not have any significant consequences. 43 That there were no episodes of transient loss of vision during measurements in this study supports the assumption that the IOP increments caused by digital forces that were involved, and their duration, appear to be safe for healthy eyes.…”
Section: Discussionsupporting
confidence: 80%
“…42 Measurement of retinal nerve fiber layer thickness in healthy patients undergoing LASIK suggests that exposure to IOP greater than 60 mm Hg for periods up to 45 seconds does not have any significant consequences. 43 That there were no episodes of transient loss of vision during measurements in this study supports the assumption that the IOP increments caused by digital forces that were involved, and their duration, appear to be safe for healthy eyes.…”
Section: Discussionsupporting
confidence: 80%
“…Roberts et al19 suggested that the changes in RNFL measurement with GDx-FCC after surgery were unlikely to be related to actual physical change to the ganglion cells, hypothesizing that the changes were artifacts due to the change in corneal birefringence after LASIK. In other studies, once VCC was applied, which accounts for the individual corneal properties, there was no difference in RNFL measurement before and after LASIK 2022. These studies raise awareness that the measurement methods must be considered when examining the relationship between CCT and RNFL thickness.…”
Section: Discussionmentioning
confidence: 76%
“…Some studies suggested that excimer laser PRK has no significant effect on RNFL measurements as determined by scanning laser polarimetry [16,17]. On the other hand, a series of studies suggested that LASIK exert non-significant impact on RNFL as well; however, the majority of them had short follow-up periods or moderate number of subjects [18][19][20].…”
Section: Introductionmentioning
confidence: 99%